Grape variety comparison of different stress tolerance based on the quantitative measurement of carbohydrates - Kovács-Nagy, E.; Bilek, A.; Lacz, E.; Bodor, P.; Sárdi, É. (International Journal of Horticultural Science, 2008)
The analyses of various host-pathogen relationships have established the response reaction roles of carbohydrates — especially monosaccharides — measurable in the vegetal parts of the host. Published results also provide information concerning the way various pathogens utilize carbohydrates and concerning the carbohydrates pathogens prefer out of the "selection" provided by the host plant. The role of carbohydrates in the response reactions to abiotic stress has been studied on several plant species as well — currently, too, it is an often discussed area of research. The above-mentioned results form the basis of our intention to study the connection between susceptibility to grey mould and the quantity of measurable carbohydrates in the leaves of grape varieties of various stress tolerance levels.